Adolescents at risk of mental health problems in the COVID‐19 pandemic: A prospective population‐based study of the effects of government mandates and school closures. Issue 1 (8th January 2023) - Mundy, Lisa K.; Canterford, Louise; Dashti, S. Ghazaleh; Husin, Hanafi Mohamad; Beatson, Ruth; Edwards, Ben; Patton, George C.
Abstract: There is increasing evidence that the COVID‐19 pandemic has had substantial mental health impacts for adolescents. Yet, few definitive studies have investigated which adolescents were at higher risk of poor mental health and well‐being during the pandemic. Data were drawn from the Childhood to Adolescence Transition Study, a prospective cohort study of students in Australia ( N = 1211). Prevalence of mental health outcomes (depressive symptoms, anxiety symptoms, self‐harm and good subjective well‐being) was estimated in school Years 5–12, where Years 11 (2020) and 12 (2021) coincided with the pandemic. The age‐ and sex‐adjusted relative risk of each mental health outcome for each priority group during the pandemic were estimated. During the pandemic, over 50% of study participants reported depressive symptoms, and one quarter reported anxiety symptoms. There was a decrease in good subjective well‐being compared with pre‐pandemic years, while self‐harm prevalence remained similar. History of mental health problems, school disengagement and frequent peer victimisation increased the risk of experiencing mental health problems during the pandemic. Schools play a central role in maintaining the mental health and good subjective well‐being of students, and this is particularly important during periods of social disruption, such as the COVID‐19 pandemic.